The Glycine max Conserved Oligomeric Golgi (COG) Complex Functions During a Defense Response to Heterodera glycines - Lawaju, Bisho Ram; Niraula, Prakash; Lawrence, Gary W.; Lawrence, Kathy S.; Klink, Vincent P. (Frontiers in Plant Science, 2020)
The conserved oligomeric Golgi (COG) complex, functioning in retrograde trafficking, is a universal structure present among eukaryotes that maintains the correct Golgi structure and function. The COG complex is composed of eight subunits coalescing into two sub-complexes. COGs1–4 compose Sub-complex A. COGs5–8 compose Sub-complex B. The observation that COG interacts with the syntaxins, suppressors of the erd2-deletion 5 (Sed5p), is noteworthy because Sed5p also interacts with Sec17p [alpha soluble NSF attachment protein (α-SNAP)]. The α-SNAP gene is located within the major Heterodera glycines [soybean cyst nematode (SCN)] resistance locus (rhg1) and functions in resistance. The study presented here provides a functional analysis of the Glycine max COG complex. The analysis has identified two paralogs of each COG gene. Functional transgenic studies demonstrate at least one paralog of each COG gene family functions in G. max during H. glycines resistance. Furthermore, treatment of G. max with the bacterial effector harpin, known to function in effector triggered immunity (ETI), leads to the induced transcription of at least one member of each COG gene family that has a role in H. glycines resistance. In some instances, altered COG gene expression changes the relative transcript abundance of syntaxin 31. These results indicate that the G. max COG complex functions through processes involving ETI leading to H. glycines resistance.